Development of a novel electrochemical pyroprocessing methodology for spent nuclear fuels - Stevenson, Anthony John (2017)
Nuclear power remains the most dense and reliable primary form of energy supply worldwide. Electricity generation via fission is also inherently carbon free, with environmental footprints rivalling modern renewable options. However issues arise from the production of highly irradiated spent fuels, with current management options limited to geological repository storage or, more desirably, closing of the fuel cycle by partitioning to recover fissionable species.